Bibliometric Review of Global Research on Sustainable Finance and Carbon Taxation - Firmansyah Arifin; Dimas Pratama Putra (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: Sustainable finance and carbon taxation represent a rich field of research. However, existing reviews are often constrained, offering piecemeal insights drawn from subsets of the literature rather than the entire body of work on these topics. To address this gap, this study seeks to comprehensively map the research dynamics surrounding carbon taxation and sustainable finance. By employing big data analytics and machine learning to analyze scholarly research, it explores the evolution of the field, assesses the impact of key publications, and examines collaborative efforts that drive innovation.Method: This study employs bibliometric methods, using R Studio software, to analyze publication data from 2020 to 2024. It identifies keywords, emerging trends, author collaborations, and contributions from various countries.Result: The findings reveal a significant increase in research on carbon taxation and sustainable finance, with China emerging as the largest contributor. The analysis also uncovers key trends in topics such as economic development and carbon dioxide emissions, which are central to global discussions. Furthermore, the findings emphasize the importance of international collaboration in tackling climate change and promoting economic sustainability. This study not only enriches academic literature but also offers valuable insights for policymakers, financial institutions, and other stakeholders addressing environmental and economic sustainability challenges.Practical Implications for Economic Growth and Development: This research offers valuable insights for policymakers to promote environmentally friendly economic growth strategies through carbon tax policies and sustainable finance initiatives.